2018
DOI: 10.5194/acp-2018-921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The vertical distribution of biomass burning pollution over tropical South America from aircraft in situ measurements during SAMBBA

Abstract: <p><strong>Abstract.</strong> To reduce the uncertainties in processes driving the vertical distribution of biomass burning pollutants, and thus impacts on regional weather and climate, we present an integrated analysis of vertical profiles of pollutants and meteorological parameters measured on flights during the 2012 South American Biomass Burning Analysis (SAMBBA) field experiment.</p><p> During the dry season there were significant contr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
5
0
3
Order By: Relevance
“…We assessed the effect of the anomalously high transport of pyrogenic emissions into the Amazon in 2007 and 2010 on the [CO] trend with a sensitivity analysis. Such emissions may account for up to half of the atmospheric optical depth during the dry season 52,53 , a pattern that also applies to CO 54 . The sensitivity analysis was performed by decreasing the [CO] values in 5% increments whereby we found that a 10% reduction in [CO] for the years 2007 and 2010 was sufficient to yield a significantly decreasing [CO] trend at the 95% confidence level (p value = 0.02), where time explains 40% of the variance in [CO].…”
Section: Resultsmentioning
confidence: 99%
“…We assessed the effect of the anomalously high transport of pyrogenic emissions into the Amazon in 2007 and 2010 on the [CO] trend with a sensitivity analysis. Such emissions may account for up to half of the atmospheric optical depth during the dry season 52,53 , a pattern that also applies to CO 54 . The sensitivity analysis was performed by decreasing the [CO] values in 5% increments whereby we found that a 10% reduction in [CO] for the years 2007 and 2010 was sufficient to yield a significantly decreasing [CO] trend at the 95% confidence level (p value = 0.02), where time explains 40% of the variance in [CO].…”
Section: Resultsmentioning
confidence: 99%
“…AOD measurements were taken from AERONET stations either at Manaus or Alta Floresta, depending on availability and proximity to the flight. The SAMBBA campaign (details in Brito et al., 2014 and Darbyshire et al., 2019) was based at Porto Velho with flights extending over much of the Amazon. In situ measurements from the CDP probe (http://data.ceda.ac.uk/badc/sambba/data) were used to determine flight‐mean values of N d (10th–90th percentile of data above 1 cm −3 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, between January and May, there is systematic positive bias of ~5 ppbv (although this is within the observational variability). Comparisons with aircraft observations from the South AMerican Biomass Burning Analysis campaign (Darbyshire et al, ) (September‐October 2012) show the model successfully reproduces the boundary layer vertical ozone profile between 30 and 45 ppbv, with a slight positive bias of 2–3 ppbv. These observations and comparison are also consistent with ozonesondes from Natal (2007–2008).…”
Section: Methods and Datamentioning
confidence: 79%